Green synthesis and characterization of copper oxide nanoparticles using hylocereus polyrhizus peel extract for anticancer studies on colon (hcc2998) carcinoma cells - Cheah, Qian Qian (2024)
The application of metal oxide nanoparticles in cancer treatment is considered a novel invention in the field of biomedicine, replacing traditional radiation and chemotherapy treatments. In this study, an economical and sustainable synthesis of copper oxide nanoparticles (CuO NPs) was implemented via a green approach, using the peel extraction of Hylocereus polyrhizus via freeze dried method and copper nitrate trihydrate as the precursor. The synthesized CuO NPs were characterized by analytical equipment such as UV-Visible spectroscopy (UV-Vis), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray (EDX), X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR). The analysis obtained from UV-Vis spectroscopy presented the wavelength of CuO NPs at 286 nm. A band gap energy of 4.15 eV was determined from the Tauc plot. The SEM analysis displayed 24.9 to 35.4 nm size range for the spherical nanoparticles. The EDX spectrum proved the purity of the H. polyrhizus-mediated CuO NPs. The patterns of XRD peaks showed a monoclinic lattice of CuO NPs, with a crystalline dimension of 23.62 nm. The FTIR spectrum revealed the diverse phytochemical elements found in H. polyrhizus extract, which play a crucial role as capping and reducing agents during the synthesis of CuO NPs. The cytotoxic effect of the green-synthesized CuO NPs was tested on the colon carcinoma (HCC2998) cell line via MTT assay. Cell viability was reduced with increasing concentrations of CuO NPs. CuO NPs acted in a dose-dependent mode and showed a high cytotoxic activity towards the colon carcinoma cells, whereas exhibited lesser toxicity towards the Vero cells. This study suggests that H. polyrhizus-mediated CuO NPs can be utilized as a promising cytotoxic agent in the biomedical field, because they have the potential to selectively target and kill malignant cells, while sparing normal healthy cells.